Long Non-coding RNA RMRP in the Pathogenesis of Human Disorders - Hussen, Bashdar Mahmud; Azimi, Tahereh; Hidayat, Hazha Jamal; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Cell and Developmental Biology, 2021)
RNA component of mitochondrial RNA processing endoribonuclease (RMRP) is a non-coding transcript firstly acknowledged for its association with the cartilage-hair hypoplasia (CHH) syndrome, a rare autosomal recessive condition. This transcript has been spotted in both nucleus and mitochondria. In addition to its role in the pathogenesis of CHH, RMRP participates in the pathogenesis of cancers. Independent studies in bladder cancer, colon cancer, hepatocellular carcinoma, lung cancer, breast carcinoma and multiple myeloma have confirmed the oncogenic effects of RMRP. Mechanistically, RMRP serves as a sponge for some miRNAs such as miR-206, miR-613 and miR-217. In addition to these miRNAs, expressions of tens of miRNAs have been altered following RMRP silencing, implying the vast extent of RMRP/miRNA network. In the present narrative review, we explain the role of RMRP in the development of cancers and some other non-malignant disorders.